Estudio de prefactibilidad para la instalación de una planta para el diseño y fabricación de bombas de vacío - Lescano Villegas, Wiley (2016)
This study aims to assess the technical, economic, financial and market feasibility for the implementation of a plant for the manufacture of vacuum pumps.